Survey of accounting : - Terrell, Katherene P. (Pearson/Prentice Hall, 2005)
The book presents the evolution of a fictitious business from its formation, looking first at the strategic planning and research to organize the business, financing the plan, investing in the resources, amd operating the business. As you read, you'll learn the accounting cycle culminating with the financial statements, to analyze the information for internal management decisions, and to compare the fictitious business with others